2012
DOI: 10.1603/an11123
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Species of the Anastrepha fraterculus Complex (Diptera: Tephritidae): A Multivariate Approach for the Recognition of South American Morphotypes

Abstract: Although a large amount of data have been published in past years on the taxonomic status of the Anastrepha fraterculus (Wiedemann) species complex, there is still a need to know how many species this complex comprises, the distribution of each one, and their distinguishing features. In this study, we assessed the morphometric variability of 32 populations from the A. fraterculus complex, located in major biogeographical areas from the Neotropics. Multivariate techniques for analysis were applied to the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
184
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(196 citation statements)
references
References 23 publications
7
184
0
5
Order By: Relevance
“…carambolae as a discrete entity 29 . Pluralistic approaches have been also followed for species delimitation within species complexes of other Tephritidae genera, such as the Anastrepha fraterculus complex 18, 3035 . In this context, the issue of the number and the limits of species within the FAR complex has been recently addressed by an integrative approach on the basis of: (i) adult and larvae morphology 36, 37 , (ii) wing morphometrics 38 , (iii) microsatellite analysis 8 , (iv) cuticular hydrocarbons 39 , (v) pheromones 40 , (vi) developmental physiology 41 and (vii) geographical and altitudinal distribution 42 .…”
Section: Introductionmentioning
confidence: 99%
“…carambolae as a discrete entity 29 . Pluralistic approaches have been also followed for species delimitation within species complexes of other Tephritidae genera, such as the Anastrepha fraterculus complex 18, 3035 . In this context, the issue of the number and the limits of species within the FAR complex has been recently addressed by an integrative approach on the basis of: (i) adult and larvae morphology 36, 37 , (ii) wing morphometrics 38 , (iii) microsatellite analysis 8 , (iv) cuticular hydrocarbons 39 , (v) pheromones 40 , (vi) developmental physiology 41 and (vii) geographical and altitudinal distribution 42 .…”
Section: Introductionmentioning
confidence: 99%
“…In this family, there are species of agricultural importance that are, in reality, complexes of cryptic species (Kitthawee and Dujardin 2010, Hernández-Ortiz et al 2012, Ruiz-Arce et al 2012, Schutze et al 2012, Krosch et al 2013, Vaníčková et al 2014). The occurrence of cryptic species among economically important fruit flies strongly affects the development of management tactics for these pests.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed in America and is associated with a large number of host fruits (Hernández-Ortiz et al 2012, Norrbom et al 2013). In fact, this nominal species comprises a cryptic species complex, as has been demonstrated by genetic (Steck 1991, Steck and Sheppard 1993, Smith-Caldas et al 2001) and cytogenetic (Selivon et al 2004, 2005, Goday et al 2006) studies, reproductive isolation tests (Selivon et al 1999, Vera et al 2006, Cáceres et al 2009, Devescovi et al 2014), chemo-taxonomy (Cáceres et al 2009, Břízová et al 2013, Vaníčková et al 2015) and morphological (Selivon and Perondini 1998, Selivon et al 2005, Hernández-Ortiz et al 2004, 2012) analysis. Based on adult morphology, Hernández-Ortiz et al (2012) identified seven morphotypes within this complex: Mexican, Andean, Venezuelan, Peruvian, and three morphotypes from the Brazilian territory, one of which extends to Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Anastrepha fraterculus, known to comprise a cryptic species complex (Hernández-Ortiz et al 2012;Sutton et al 2015), had the greatest number of types (n = 12). The counts for A. ludens, A. obliqua, and A. distincta each had between 2 and 3 types ( Table 1).…”
mentioning
confidence: 99%